PENGETAHUAN IBU TENTANG ALAT KONTRASEPSI DI LINGKUNGAN VII KELURAHAN SEI SIKAMBING B MEDAN SUNGGAL - Triana, Heni (Universitas Prima Indonesia, 2018)
The objective of the research was to find out the influence of health Population growth in Indonesia is growing fast enough. It can be seen from the total population in 1971, amounting to 118 million people increased rapidly became 220 ​​million in habitants in 2005, Indonesia has had problems with the amount and quality of human resources with the birth of3,000,000/year. The study design used was a quasi-experimental design with One-Group Pretest-Posttest Total population of230 people with a sample of 34 people. Data processing done by means of univariate and bivariate. To calculate the effect of the treatment is done by using a statistical test is paired sample t-test is to see the difference before and after treatmentusingcomputerizedtechniquesnamelySPSS17.0.The results showed that prior to counseling(pre-test) indicates knowledge of mothers gained a mean of13.24, standard deviation4.64, and the standard error value of0.79., Where is after counseling(Post-test) indicates knowledge of mothers obtained a mean value of20.94, a standard deviation value of3.69, and a standard error of 0.63 value. This study found a significant difference between the average level of knowledge prior to the extension after extension Expected to give a special tips when giving health education of counseling which is expected to occur a process of continuous change in behavior, so that the target does not change merely because of the addition of health in ormasi course, but it is expected also to a change in attitude at the same skill steady or action that leads to better work.